2010
DOI: 10.1093/aepp/ppp008
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Preferential Trade Arrangements on EU Imports from Developing Countries: The Case of Fresh Cut Flowers

Abstract: This study examines the effects that the Generalized System of Preferences schemes for developing countries (GSP + ) have on European Union (EU) demand for imported cut flowers. Without GSP + , a tariff would be applied to flowers from Colombia and Ecuador. Results show that Colombian carnation prices have a negative effect on EU flower expenditures, resulting in preferential treatment for Colombia being mostly trade‐creating. When a tariff is applied to Colombia, imports of Colombian carnations and Kenyan ros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Palma and Ward (2010) have studied the U.S. demand for cut flowers, potted flowering plants, and dry/artificial and outdoor flowers using simulation analysis to decompose demand into market penetration and buying frequency. Muhammad et al have analyzed the effects of different tariff regimes on the EU demand for imported cut flowers (Muhammad, 2009;Muhammad, Amponsah, and Dennis, 2010;Muhammad, D'Souza, and Amponsah, 2013).…”
mentioning
confidence: 99%
“…Palma and Ward (2010) have studied the U.S. demand for cut flowers, potted flowering plants, and dry/artificial and outdoor flowers using simulation analysis to decompose demand into market penetration and buying frequency. Muhammad et al have analyzed the effects of different tariff regimes on the EU demand for imported cut flowers (Muhammad, 2009;Muhammad, Amponsah, and Dennis, 2010;Muhammad, D'Souza, and Amponsah, 2013).…”
mentioning
confidence: 99%
“…A number of studies have explored the utilization of the preferential regimes and assessed the impacts of those regimes on agricultural or seafood trade flows (Guillotreau & Peridy, 2000;Asche, 2001;Brester, Marsh, & Smith, 2002;Panagariya, 2002;Bureau, Chakir, and Gallezot 2007;Muhammad, 2007 andAgostino, Demaria, and Trivieri 2010;Muhammad, Amponsah, and Dennis 2010;Serrano, and Pinilla 2014). Of them, Bureau, Chakir, and Gallezot (2007) provided evidence of the high utilization of the EU and the US GSP schemes in the agricultural, food, and fisheries sectors.…”
Section: [Table 1 Here]mentioning
confidence: 99%
“…This research contributes to a broader literature on the implications of free trade agreements and specific agricultural sectors (Lee, Seale, and Jierwiriyapant 1990; Muhammad, Amponsah, and Dennis 2010; Cardamone 2011; Muhammad, Countryman, and Heerman 2018). Muhammad, Countryman, and Heerman (2018) examined Japanese beef demand by source and the implications of tariff reforms in the Japan-Australia Economic Partnership Agreement.…”
Section: Introductionmentioning
confidence: 81%
“…Cardamone (2011) examined the impact of preferential trade agreements on monthly exports of specific fruits to the EU and found that agreement effects varied by commodity. Muhammad, Amponsah, and Dennis (2010) analyzed the impacts of preferential arrangements for developing countries on EU demand for imported cut flowers. Lee, Seale, and Jierwiriyapant (1990) examined Japanese import demand for citrus and how more liberal trade could impact U.S. citrus exports relative to exports from competing countries like Brazil and Israel.…”
Section: Introductionmentioning
confidence: 99%